Association between theory of mind and mental state talk in preschoolers and later social competence and behaviour - Barreto, A. L.; Osório, A.; Baptista, J.; Fearon, P.; Martins, C. (Infant and Child Development, 2018)
This study had 2 primary aims: (a) to investigate the concurrent links between preschool-aged children's theory of mind (ToM) and mental state talk at 55months and (b) to examine the longitudinal associations between preschool-aged children's social understanding, as indicated by their ToM, and mental references, and their later social competence and behaviour at 69months. Participants included 73 children and their mothers. ToM was assessed using a battery that consisted of 6 standardized tasks, and social competence and behaviour were assessed via teacher ratings. We observed an association between children's ToM and their mental state talk, specifically regarding cognition references during interactions with their mothers. Moreover, both children's ToM and mental references were longitudinally related to social competence and behaviour but only in girls. Our results support that ToM, which was assessed using false belief tasks, and the child's tendencies to refer to mental states during everyday interactions are 2 important related markers of children's social understanding and that both are linked to children's social competence and behaviour. The importance of considering gender-specific effects when investigating children's social cognition is also highlighted.